The Application of Blockchain in the Accounting Industry - Yunan Bai (Journal of World Economy, 2024)
Blockchain technology is one of the new information technologies, because of its consensus mechanism, distributed mechanism, smart contract and other technical characteristics, as well as non-forgery, open and transparent, traceability, whole-process traces, collective maintenance and other characteristics, has been widely concerned by various industries. Accounting is the language of business and a management information system that provides financial and accounting information. In today’s highly developed market economy, accounting plays an indispensable and important role. The in-depth application of blockchain technology in the accounting industry can promote the development of the accounting industry, but also can promote the integration of blockchain technology into the overall social and economic environment. This paper studies the application of blockchain technology in the accounting industry. “Luckin coffee financial fraud” events as examples, by analyzing the Luckin coffee event accounting problems, put forward the problems existing in the traditional way of accounting, and block chain technology used in comparing the advantage of the accounting profession, points out that block chain technology can solve the problem of some of the existing accounting, to perfect the accounting and internal control to provide a better strategy and scheme. At the same time, this paper also analyzes the risks existing in the application of blockchain technology in the accounting industry, and briefly puts forward several countermeasures. Finally, the development of block chain technology into the accounting industry is prospected. Blockchain technology not only promotes the development of traditional financial accounting, but also promotes the development of management accounting, and promotes the overall reform of the accounting industry.